Associations between the performance of scoring manoeuvres and lower-body strength and power in elite surfers - Secomb, J. L.; Farley, O. R. L.; Lundgren, L.; Tran, T. T.; King, A.; Nimphius, S.; Sheppard, J. M.; Meir, R.; Triplett, T. (International Journal of Sports Science and Coaching, 2015)
The purpose of this study was to determine whether any significant associations were present between lower-body strength and power, and the performance of turning and aerial manoeuvres in elite surfing athletes. Eighteen competitive male surfers performed a battery of physical tests (countermovement jump (CMJ), squat jump (SJ), and isometric mid-thigh pull (IMTP)) during a single session, in addition to having their performance of turning and aerial manoeuvres ranked from highest to lowest. Significant associations were identified between turning manoeuvre ranking and; peak force in the CMJ, SJ and IMTP (?=-0.737, p<0.01; ?=-0.856, p<0.01; ?=-0.683, p<0.01, respectively), as well as, peak velocity and jump height in the CMJ (?=-0.560, p=0.02; ?=-0.529, p=0.02, respectively). No significant associations were identified between aerial manoeuvre ranking and any strength and power variables. These results suggest that surfing athletes that exhibit greater lower-body isometric and dynamic strength, and power also perform higher scoring turning manoeuvres during wave riding. ABSTRACT FROM AUTHOR